The Risk of Transfusion of Transmissible HIV Infections in Sokoto, the North West of Nigeria - U-K, Muhammad; H, Raji; R. H, Muhammad; A, Faruq; AS, Baki (Asian Journal of Pharmaceutical Research and Development, 2021)
The risk of transfusion of transmissible HIV infection was investigated amongst potential blood donors from three health care institutions in Sokoto, North West Nigeria. Three hundred and fifty (350) blood samples from study subjects were screened for HIV antibody using Determine kit for HIV 1&2 (by Alere) and Uni-gold kit (biotech) for second antibody screening. All blood samples negative for the HIV antibodies using RDT were further screened for thep24 antigen using Enzyme Linked Immunosorbent Assay (ELISA). The results obtained showed that blood samples from 3(0.9%) study subjects were sero-positive for HIV antibody using the serial algorithm. There was no statistically significant difference (p=1.000) between the two RDT screening kits used. Nine blood donors 9(2.6%) were positive for HIV-1 p24-antigen using ELISA test. Overall results showed that the prevalence rate of HIV was 3.4% amongst all study subjects. However, sensitivity and specificity of RDT was 3.4% and 96% while the positive and negative predictive value was 100% and 97% respectively. The low incidence of 0.9% obtained using RDT clearly indicates that the antibody tests had failed to detect the newly infected blood donors. This is confirmed by the more sensitive and specific p24 antigen test.Thus, the risk of transmitting undetected HIV antigens from such sero-negative blood samples is expectedly high. Even though transmission of blood and blood products is a routine in our health care settings, it should only be done when benefit clearly outweighs the risk.